Technology Entrepreneurship Project (ENT 600) : Steel Recon Industries Sdn. Bhd. / Mudrikah Ab Mahadi - Ab Mahadi, Mudrikah (2022)
Smoke detectors will alert you to a fire even if you are sleeping, distracted, or in another part of the house than where the fire is. When you are awake, they give you extra alert time, and if you are sleeping, they will wake you up. Many people believe that if there is a fire in their house, they can smell smoke and wake up, but this is not true. Many fires emit odourless gasses that are highly poisonous. Sleeping people can be overwhelmed by these gasses without ever waking up. Smoke detectors include life-saving alerts, allowing you to escape before being trapped by fire or smoke. Smoke alarms, also known as smoke detectors, operate by continuously scanning the air for signs of gasses and smoke particles created by a fire.